Field‐Driven Reversal Models in Artificial Spin Ice. Issue 7 (3rd June 2021) - Paterson, Gary W.; Macauley, Gavin M.; Macêdo, Rair
Abstract: A set of topological arrangements of individual ferromagnetic islands in ideal and disordered artificial spin ice (ASI) arrays is investigated in order to evaluate how aspects of their field‐driven reversal are affected by the model used. The set contains the pinwheel and square ice tilings, and thus a range of magnetic ordering and reversal properties are tested. It is found that a simple point dipole model performs relatively well for square ice, but it does not replicate the properties observed in recent experiments with pinwheel ice. Parameterization of the reversal barrier in a Stoner–Wohlfarth model improves upon this, but fails to capture aspects of the physics of ferromagnetic coupling observed in pinwheel structures which have been attributed to the non‐Ising nature of the islands. In particular, spin canting is found to be important in pinwheel arrays, but not in square ones, due to their different symmetries. The authors' findings will improve the modeling of ASI structures for fundamental research and in applications which are reliant upon the ability to obtain and switch through known states using an externally applied field. Abstract : The collective behaviors of arrangements of ferromagnetic islands in artificial spin ices (ASIs) are of great interest in applications. The point dipole approximation has been the mainstay of numerical simulations of ASI systems due to its efficiency. By comparing this approach to more expensive micromagnetic modeling of the interactions, important contributions to key aspects of emergent phenomena are identified.